Male callers to an Australian perinatal depression and anxiety help line—Understanding issues and concerns. Issue 1 (16th September 2019) - Fletcher, Richard; StGeorge, Jennifer; Newman, Louise; Wroe, Jaime
ABSTRACT: There is increasing recognition of the issues facing men in the perinatal period. Vulnerability factors and issues in the partner relationship contribute to mental health risk and can impact the quality of the father–infant relationship. Yet, there is limited understanding of fathers' help‐seeking when they or their partner are experiencing mental health issues in the context of caring for a new baby. The present study examines fathers' contacts with the Perinatal Anxiety and Depression Australia (PANDA) National Helpline. The study reviewed contacts from fathers and their identified needs for assistance, relationship issues, and support needs; 70% of male callers ( N = 129) reported concerns about the mother's mental health, and 57% were concerned about relationship breakdown. Significant numbers of men raised issues about their own mental health (43%) and many were concerned about the impact of maternal mental state on the relationship with the infant. When compared to community data, there were elevated rates of concerns about depression and anxiety. Men also described difficulties with the fathering role and with regulating their own feelings of guilt and frustration. These findings highlight the needs of men for support when a mother experiences perinatal problems and also the risk for distress in fathers. RESUMEN: Hay un incremento en el reconocimiento de los asuntos que enfrentan los hombres en el período perinatal.  Los factores de vulnerabilidad y asuntos en la relación con la pareja contribuyen al riesgo de salud mental y pueden tener impacto en la calidad de la relación papá‐infante.  Aun así, hay una comprensión limitada acerca de la búsqueda de ayuda por parte de los papás cuando ellos o sus parejas están experimentando asuntos de salud mental en el contexto de cuidar a un nuevo bebé.  El presente estudio examina el contacto de los papás con la línea de ayuda nacional Ansiedad y Depresión Perinatal Australia (PANDA). El estudio revisó contactos de papás y sus identificadas necesidades para la asistencia, asuntos de la relación y necesidades de apoyo: 70% de los varones que llamaron (N = 129) reportaron preocupaciones acerca de la salud mental de la madre y 57% estaban preocupados acerca del rompimiento de la relación.  Un significativo número de hombres presentaron asuntos acerca de su propia salud mental (43%) y muchos estaban preocupados sobre el impacto del estado mental materno en la relación con el infante. Cuando se compara con la información comunitaria, hubo puntajes elevados de preocupaciones acerca de la depresión y la ansiedad. Los hombres también describieron dificultades con el papel de ser padres y con la forma de regular sus propios sentimientos de culpa y frustración.  Estos resultados subrayan las necesidades de los hombres de apoyo cuando una madre experimenta un problema perinatal y también el riesgo de angustia en los papás. RÉSUMÉ: Les problèmes auxquels font face les hommes durant la période périnatale sont de plus en plus reconnus. Des facteurs et des problèmes de vulnérabilité dans la relation au partenaire contribuent au risque de santé mentale et peuvent avoir un impact sur la qualité de la relation père‐enfant. Cependant on n'a que des connaissances limitées de l'appel à l'aide des pères lorsqu'ils font ou lorsque leur partenaire fait l'expérience de problèmes de santé mentale dans le contexte du soin à un nouveau‐né. Cette étude a examiné les contacts des pères avec la ligne téléphonique nationale australienne pour l'anxiété et la dépression périnatales, abrégée PANDA selon l'anglais. Cette étude a passé en revue les contacts de pères et leurs besoins identifiés d'assistance et de soutien pour des problèmes liés à une relation: 70% des hommes ayant téléphoné (N = 129) ont fait état d'inquiétude à propos de la santé mentale de la mère et 57% étaient inquiets de la désintégration de la relation. Un nombre important d'hommes ont parlé de leur propre santé mentale (43%) et beaucoup d'entre eux étaient inquiets à propos de l'impact de l'état mental maternel sur la relation avec le nourrisson. Comparé aux données communautaires, on a trouvé des niveau élevés d'inquiétude sur la dépression et l'anxiété. Ces hommes ont aussi décrit des difficultés avec le rôle de père et avec la régulation de leurs propres sentiments de culpabilité et de frustration. Ces résultats mettent en évidence les besoins qu'ont les hommes de soutien quand une mère fait l'expérience d'un problème périnatal, et aussi le risque de détresse chez les pères. ZUSAMMENFASSUNG: Sorgen männlicher Anrufer bei einer nationalen Beratungsstelle für perinatale psychische Gesundheit Die Probleme, mit denen Männer in der perinatalen Phase konfrontiert sind, erfahren zunehmend Anerkennung. Vulnerabilitätsfaktoren und Probleme in der Paarbeziehung tragen zum psychischen Gesundheitsrisiko bei und können die Qualität der Vater‐Kind‐Beziehung beeinträchtigen. Allerdings gibt es bis jetzt nur wenig Untersuchungen zu hilfesuchendem Verhalten von Vätern, wenn sie oder ihre Partnerin psychische Probleme im Zusammenhang mit der Betreuung eines Neugeborenen haben. Die vorliegende Studie untersuchte Kontakte von Vätern mit der nationalen Beratungsstelle für perinatale Angst und Depression in Australien (Perinatal Anxiety and Depression Australia National Helpline; PANDA). Die Studie untersuchte Kontaktaufnahmen von Vätern hinsichtlich Beziehungsprobleme und des ermittelten Unterstützungsbedarfs: 70% der männlichen Anrufer (N = 129) gaben an, Bedenken hinsichtlich der psychischen Gesundheit der Mutter zu haben, und 57% waren über einen Zusammenbruch der Beziehung besorgt. Eine beträchtliche Anzahl von Männern äußerte Bedenken hinsichtlich ihrer eigenen psychischen Gesundheit (43%) und viele waren besorgt über die Auswirkungen des mütterlichen Geisteszustands auf die Beziehung zum Säugling. In Hinblick auf Vergleichsstichproben gab es eine erhöhte Rate an Bedenken hinsichtlich Depressionen und Angst. Männer beschrieben auch Schwierigkeiten mit der Vaterrolle und mit der Regulierung ihrer eigenen Schuld‐ und Frustrationsgefühle. Diese Befunde verdeutlichen den Unterstützungsbedarf von Männern, wenn eine Mutter unter perinatalen Problemen leidet, und das Leidensrisiko bei Vätern. 抄録: 全豪周産期メンタルヘルスの悩み電話相談に発信した男性の心配事 周産期に関わる男性が直面する問題点についての認識が広がっている。パートナーとの関係性における脆弱な要因や問題点はメンタルヘルスの危機の原因となり、また父親と乳児の関係性に質的な影響を及ぼし得る。しかしながら、父親やパートナーが生まれたての乳児のケアをする状況でメンタルヘルスの問題を経験している際、父親が援助を要請することへの理解は乏しい。本研究では、全豪悩み電話相談に発信した父親に対し Perinatal Anxiety and Depression Australia (PANDA) についての聞き取り調査を行った。研究は、父親からの聞き取りと確認された支援の必要性、関係性の問題点、そして協力の必要性について検討した。電話をかけた男性 (N = 129) の 70% は母親のメンタルヘルスについての心配事、また 57% は関係性が崩壊することについて心配していた。かなりの数の男性 (43%) は、自身のメンタルヘルスについての問題点を挙げ、また多くの男性は母の精神状態が乳児との関係性に与える影響について心配していた。一般人口に比べ、抑うつや不安に関する懸念は高率に認められた。男性はまた、父親役割の困難さや罪悪感や挫折感の調整の困難さについても語っていた。この知見は、母親が周産期の悩みを経験する際に男性が協力を必要とすること、そして父親のストレスがリスクになることについても強調している。 摘要: 男性求助者對全國圍產期心理健康熱線的關注。 我們越來越認識到圍產期父親面臨的問題。伴侶關係中的脆弱性因素和問題, 會增加心理健康風險, 並可能影響父母關係的質量。但是, 對於父親或他們的伴侶, 在照顧新生嬰兒時, 遇到心理健康問題尋求幫助的了解有限。本研究調查父親與澳大利亞圍產期焦慮和抑鬱症 (PANDA) 國家服務專線的聯繫。這項研究審查父親的聯繫方式, 以及他們的援助需求丶關係問題和支持需求: 70％ 的男性來電者 (N = 129) 表示擔心母親的心理健康, 而 57％ 的人擔心關係破裂。大量男性提出有關自身心理健康的問題 (43％), 許多人擔心母體心理狀態與嬰兒關係的影響。與社區數據比較, 父親對抑鬱和焦慮的擔憂率較高。男性求助者還描述在擔任父親的角色以及調節自己的內咎和挫敗感方面的困難。這些發現凸顯了當母親遇到圍產期問題時, 男性需要支持的需求, 以及父親的困苦風險。 ملخص: مخاوف المتصلين الذكور في مكالماتهم مع الخط الساخن القومي لدعم الصحة النفسية ما قبل الولادة. هناك اعتراف متزايد بالقضايا التي يواجهها الرجال في فتره ما قبل الولادة. وتسهم عوامل الضعف والمسائل المتعلقة بعلاقة الشريك في مخاطر الصحة النفسية ويمكن ان تؤثر علي نوعيه العلاقة بين الأب والرضيع. ومع ذلك ، فان هناك فهم محدود لمسألة طلب الآباء للمساعدة عندما يواجهون مشاكل في الصحة النفسية لهم أو للشريك في سياق رعاية طفل جديد. وتبحث هذه الدراسة اتصالات الاباء مع خط المساعدة القومي الخاص بالقلق والاكتئاب في أستراليا (PANDA). واستعرضت الدراسة اتصالات الاباء واحتياجاتهم المحددة للمساعدة وقضايا العلاقات واحتياجات الدعم: 70 في المائة من المتصلين الذكور (العدد = 129) ابلغوا عن مخاوف بشان صحة الام النفسية و 57 في المائة قلقون بشان انهيار العلاقات. وأثارت اعداد كبيره من الرجال قضايا تتعلق بصحتهم النفسية (43 في المائة) وكان الكثيرون يشعرون بالقلق إزاء تاثير الحالة النفسية الاموميه علي العلاقة مع الرضيع. بالمقارنة مع بيانات المجتمع ، كانت هناك معدلات مرتفعه من المخاوف بشان الاكتئاب والقلق. ووصف الرجال أيضا الصعوبات التي تكتنف الدور الأبوي وتنظيم شعورهم بالذنب والإحباط. وتسلط هذه النتائج الضوء علي احتياجات الرجال للحصول علي الدعم عندما تتعرض الام لمشكله ما قبل الولادة وكذلك لخطر الشعور بالكآبة عند الاباء.